2020 - an year to forget or to remember? - Ferreira, José Luís (Journal of the Portuguese Society of Anesthesiology, 2021)
The authors reflect on 2020 events, marked by the COVID19 pandemy, with concerns of some changes in our daily practice and the lack of scientific foundation of these cahges. At the end they propose a look to the future as an opportunity for change.